Effect of the nature of nanoparticles on the photophysicochemical properties and photodynamic antimicrobial chemotherapy of phthalocyanines - Magadla, Aviwe (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
In this work, the syntheses and characterisation of Zn monocaffeic acid tri"“tert"“butyl phthalocyanine (1), Zn monocarboxyphenoxy tri"“ tert"“butylphenoxyl phthalocyanine (2), tetrakis phenoxy N,N-dimethyl-4-(methylimino) phthalocyanine indium (III) chloride (3) and tetrakis N,N-dimethyl-4-(methylimino) phthalocyanine indium (III) chloride (5) are presented. Complexes 3 and 5 were further quartenised with 1,3- propanesultone to form corresponding complexes (4) and (6), respectively. Complexes 1 and 2 were covalently linked to amino functionalised nanoparticles (NPs). Complexes 3, 4, 5 and 6 where linked to oleic acid/oleylamine capped (OLA/OLM) silver-iron dimers (Ag-Fe3O4 OLA/OLM) and silver-iron core shell (Ag@Fe3O4 OLA/OLM) NPs via interaction between the nanoparticles and the imino group on the phthalocyanines. The phthalocyanine-NP conjugates afforded an increase in triplet quantum yields with a corresponding decrease in fluorescence quantum yield as compared to the phthalocyanine complexes alone. Complexes 3, 4 and their conjugates were then used for photodynamic antimicrobial chemotherapy on E. coli. The zwitterionic photosensitiser 4 and its conjugates showed better efficiency for photodynamic antimicrobial chemotherapy compared to their neutral counterparts.
Keywords: Nanoparticles; Phthalocyanines; Anti-infective agents -- Therapeutic use; Photochemotherapy; Photochemistry